PROFITABILITY AND ITS EFFECT ON STOCK PRICE SIZE OF PHARMACEUTICAL COMPANIES IN THE PERIOD 2014-2019 BEI - Rina Fiani Dwi Kurnia; Nahruddien Akbar (Universitas Muhammadiyah Makassar, 2021)
This study aims to analyze the effect of Profitability (ROA) and Company Size on the Stock Prices of pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2019. The sample in this study were 8 pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2019. This research uses purposive sampling method. The statistical methods used are the classical assumption test, multiple linear regression analysis, descriptive analysis, verification analysis and hypothesis testing. Partial testing (t-test) shows that profitability has a significant effect on stock prices. This can be proved by the results of t test of 3.428 t table 2.012 and a significance value of 0.001 alpha 0.05. While partially (t-test) shows that the size of the company does not have a significant effect on stock prices. This is evidenced by the results of the t test of -count -1.427 table 2.012 and a significance value of 0.160 alpha (0.05). In simultaneous testing (F test), profitability and company size have a significant influence on stock prices with F test results of Fcount 6.375 Ftable 3.20 and a significance value of 0.004 alpha 0.05. So this research proves that profitability affects stock prices and company size is proven to have no effect on stock prices